Greece : Athens and the mainland - Charmei, Amber (Eyewitness travel guides., 2024)
Discover a land steeped in myth and legend. Whether you plan to watch the sun sink behind the marble columns of the Parthenon in Athens, visit iconic archaeological sites such as Delphi and Olympia, or simply soak up the sun on the sandy beaches of Halkidiki, your DK Eyewitness travel guide makes sure you experience all that mainland Greece has to offer. World-class museums and archaeological sites may be the first things that come to mind when you think of Greece, but there are things both old and new to explore. Take Europe's oldest city, for example: Athens has a youthful energy and buzzing nightlife, where upmarket restaurants stand alongside traditional grill eateries and old-school ouzeris jostle with the trendy cocktail bars of up-and-coming urban neighbourhoods. Meanwhile Thessaloniki, Greece's second-largest city, awes visitors with its Byzantine churches and vibrant contemporary art scene. Our updated guide brings Greece to life, transporting you there like no other travel guide does with expert-led insights, trusted travel advice, detailed breakdowns of all the must-see sights, photographs on practically every page, and our hand-drawn illustrations which place you inside the country's iconic buildings and neighbourhoods.